The attitude of extreme right-wing movements in France to Ukraine during the Liberation Struggles of 1917-1921 (on the example of the newspaper «L’Action française») - Shkabura, Yaroslav (Вісник гуманітарних наук, 2025)
The study of the image of Ukraine in the French far-right press, in particular in the newspaper “L’Action française”, allows us to reveal a complex and heterogeneous system of perception of the Liberation Struggles in Ukraine (events of the period of the national liberation struggle of the Ukrainian people during 1917-1921) in the ideological environment of the monarchist and integral-nationalist movement. Based on the analysis of newspaper publications, it can be argued that the tone and rhetoric of materials on the Ukrainian issue changed under the influence of both the military-political situation in Eastern Europe and the internal priorities of the Action Française movement itself, which saw in world events primarily a reflection of its own concept of the fight against the republican system and “revolutionary chaos”. In the first months of revolutionary changes in Russia and the emergence of the Central Rada, the Ukrainian issue in the publication was mainly considered through the prism of the general crisis of the “imperial order” and the danger of “anarchy”, which threatened not only Eastern Europe, but also the entire Christian West. However, over time, as Ukrainian governments sought external allies, texts began to appear in the newspaper that recognized the independence aspirations of Ukrainians, especially when they coincided with France’s geopolitical interests in confronting Bolshevism. It is important that the representation of Ukraine in the pages of “L’Action française” was not autonomous — it was always subordinated to a broader narrative in which anti-Marxist and anti-democratic motives played a key role. The Ukrainian movement was presented either as an example of “order and discipline” in alliance with traditional European forces, or as another manifestation of the “decomposable” power of the revolution, if its actions contradicted the political sympathies of the editorial staff. This gives reason to believe that for the French far-right of that time, the image of Ukraine was not so much a realistic picture of events as a tool for confirming their own political theses. Thus, the analysis revealed the duality of the position of “L’Action française”: on the one hand, an ideological interest in opposing the Bolshevik threat, which could generate situational support for Ukrainian independence; on the other, a deep distrust of any forms of national self-determination outside the monarchical model, which limited the depth and stability of the positive image of Ukraine. The study also showed that the newspaper rhetoric of this period reflected political realities, but also formed a specific vision of the Ukrainian question in French public opinion, which in the following decades influenced the range of right-wing conservative interpretations of events in Eastern Europe.